P158 Fungal airway colonisation in cystic fibrosis patients in the Institute for Respiratory Diseases in Children - Skopje, Republic of North Macedonia - Arnaudova Danevska, Ivana; Jakjovska, Tatjana; Momchilovikj, Sonja; Vidoevska, A.; Popova, Gorica; Gjinovska Tasevska, Elena; Arnaudov, Dimitar (Elsevier BV, 2021)
Respiratory tract of cystic fibrosis (CF) patients has polymicrobial colonisation. Clinical impact of the fungal colonisation in CF patients is still much less understood. Here, we provide epidemiological data of fungal airway colonisation in CF patients in CF department in the Institute for Respiratory Diseases in Children in Skopje, Republic of North Macedonia.